Prefabricated versus conventional construction: Comparing life-cycle impacts of alternative structural materials. (September 2021) - Tavares, V.; Soares, N.; Raposo, N.; Marques, P.; Freire, F.
Abstract: Prefabrication can have advantages in terms of materials and time efficiency, but the overall environmental and cost trade‐offs between the two construction methods are unclear and influenced by the choice of the structural material. A life cycle assessment was carried out to compare two constructive systems (prefabrication and conventional) and different structural materials for a single-family house. Impacts, waste, costs, and production time were assessed for two prefabricated construction systems – lightweight steel frame (LSF) and wooden frame (WF) – and two conventional construction systems – reinforced concrete (RC1) with a single layer concrete block or with a double-layer brick external wall (RC2). Results showed that WF has the lowest impacts followed by LSF, and that embodied impacts can represent more than half of total impacts. Prefabricated houses have up to 65% less embodied impacts, and end-of-life impacts of prefabricated LSF are lower due to recycling; thus, unveiling the importance of embodied and end-of-life phases. Prefabrication can decrease impacts, materials consumption, and waste generation, pushing forward circularity within the construction sector. Graphical abstract: Image 1 Highlights: Comparing prefabricated (wood and LSF) and conventional (concrete) construction. Assessing life cycle environmental impacts, costs, waste, and production time. WF has the lowest energy and environmental impacts, while RC has the highest. LSF has the lowest life cycle cost, while WF has the highest. Prefabrication generates five times less waste and can boost the circular economy.